Long-chain n-3 fatty acids as an essential link between musculoskeletal and cardio-metabolic health in older adults. Issue 1 (8th February 2020) - Witard, Oliver C.; Combet, Emilie; Gray, Stuart R.
Abstract : This narrative review aims to critically evaluate scientific evidence exploring the therapeutic role(s) of long-chain n -3 PUFA in the context of ageing, and specifically, sarcopenia. We highlight that beyond impairments in physical function and a lack of independence, the age-related decline in muscle mass has ramifications for cardio-metabolic health. Specifically, skeletal muscle is crucial in regulating blood glucose homeostasis (and by extension reducing type 2 diabetes mellitus risk) and providing gluconeogenic precursors that are critical for survival during muscle wasting conditions (i.e. AIDS). Recent interest in the potential anabolic action of n -3 PUFA is based on findings from experimental studies that measured acute changes in the stimulation of muscle protein synthesis (MPS) and/or chronic changes in muscle mass and strength in response to fish oil-derived n -3 PUFA supplementation. Key findings include a potentiated response of MPS to amino acid provision or resistance-based exercise with n -3 PUFA in healthy older adults that extrapolated to longer-term changes in muscle mass and strength. The key mechanism(s) underpinning this enhanced response of MPS remains to be fully elucidated, but is likely driven by the incorporation of exogenous n -3 PUFA into the muscle phospholipid membrane and subsequent up-regulation of cell signalling proteins known to control MPS. In conclusion, multiple lines of evidence suggest that dietary n -3 PUFA provide an essential link between musculoskeletal and cardio-metabolic health in older adults. Given that western diets are typically meagre in n -3 PUFA content, nutritional recommendations for maintaining muscle health with advancing age should place greater emphasis on dietary n -3 PUFA intake.